(untitled) (Nóema, 2024)
My aim in this article is to shed light on Peirce’s theory of vagueness. Peirce has been largely excluded from the analytical debate on vagueness, which seeks to classify it from a disciplinary perspective as if it were a problem of exclusive fields. The Sorites paradox is a key reference for contemporary analytical theories of vagueness, which see in it their historical origin and their main target. Peirce approached vagueness in a very different way, treating it transdisciplinarily, seeing its semiotic, epistemological and metaphysical potential. For Peirce, too, vagueness has to do with propositions, but the field of investigation is wider and the perspective broader. Here I focus on the first two: the first paragraph after the introduction is intended to situate the debate on vagueness both historically and theoretically. In the second, I focus on the vagueness inherent in the propositional subject by analysing its semiotic effects, while in the third, I investigate the vagueness of the propositional predicate by emphasising its epistemological consequences.